The NHS clinical governance support team : a five year focus. - Halligan, Professor Aidan (Emerald Group Pub., 2006)
For the last five years the NHS Clinical Governance Support Team (CGST) has been at the forefront of supporting NHS organisations in delivering clinical governance. Promoting systems to ensure people receive safe, high quality, patient centred care; embedding the necessary modernisation and improvement within organisations, and supporting the cultural change to do so. CGST staff have gained a considerable amount of insight into the experiences of frontline staff who succeed in implementing clinical governance and service modernisation. In recognition of the contribution the CGST has made, and.